2012
DOI: 10.1074/jbc.m112.395574
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting the Unique Methylation Pattern of Androgen Receptor (AR) Promoter in Prostate Stem/Progenitor Cells with 5-Aza-2′-deoxycytidine (5-AZA) Leads to Suppressed Prostate Tumorigenesis

Abstract: Background: There is a specific silencing of AR gene expression in prostate stem cells. Results:The induction of AR gene expression inhibited the self-renewal of the prostate stem cells. Conclusion:The induction of AR expression suppressed PCa stem cell-mediated tumorigenicity. Significance: This is the first attempt to suppress prostate cancer growth via epigenetic modification of AR genes in PCa stem cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 59 publications
4
46
1
Order By: Relevance
“…Treatment of prostate cancer stem cells with Aza-dC led to an up-regulation of AR and a decrease in proliferation and tumor formation. Moreover, Aza-dC treatment also induced differentiation of the cancer stem cells, which is correlated with a reduced expression of stem cell-associated genes OCT4 and NANOG [92] . Thus, this study suggests that the inhibition of DNA methylation might be clinically translated for patients having prostate cancers with androgen-independent feature.…”
Section: Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of prostate cancer stem cells with Aza-dC led to an up-regulation of AR and a decrease in proliferation and tumor formation. Moreover, Aza-dC treatment also induced differentiation of the cancer stem cells, which is correlated with a reduced expression of stem cell-associated genes OCT4 and NANOG [92] . Thus, this study suggests that the inhibition of DNA methylation might be clinically translated for patients having prostate cancers with androgen-independent feature.…”
Section: Prostate Cancermentioning
confidence: 99%
“…The inhibitory role of AR in aggressiveness of prostate cancer is supported by loss of AR expression via promoter DNA methylation [88][89][90][91] . Interestingly, expression of AR is also reduced in prostate cancer stem cells particularly with high CD133 expression level [92] . Treatment of prostate cancer stem cells with Aza-dC led to an up-regulation of AR and a decrease in proliferation and tumor formation.…”
Section: Prostate Cancermentioning
confidence: 99%
“…Tian et al (12) showed a link between AR gene methylation and prostate cancer progression. These authors found that AR gene methylation in promoter regions was likely related to prostate stem/progenitor cell stemness and differentiation.…”
Section: Epigenetic Modulation Of Ar Gene Expression In Prostate Cancmentioning
confidence: 99%
“…29 In accord with these findings, 5-aza-29-deoxycytidine, which can effectively inhibit the methylation of the AR promoter, was reported to be an effective agent in the suppression of refractory progressions. 30 Changes in miRNA are also involved in the progression of CRPC.…”
Section: Mechanism Of Pca Progressionmentioning
confidence: 99%